BUS TICKET BOOKING INFORMATION SYSTEM - Setya Chendra Wibawa; Doni Abdul Fatah; Moch. Mifahul Huda Firmansyah; Nur H. Mustafit; Dini L. A.; Eka R. Putri; Cholik Setyo Laksono (International Journal of Science, Engineering, and Information Technology, 2021)
This article was written during the covid pandemic, during a pandemic like this one's mobility is being limited. So that it has a big impact on activities that are usually carried out, including the case in the field of transportation. In this case, people tend to reduce being outside their homes and also avoid crowds to minimize exposure to the Covid-19 virus. This also affects the sale of vehicle tickets from various aspects ranging from air, land and sea. To overcome this problem, a bus ticket booking website was created. With this bus ticket booking website, tickets can be purchased without having to come directly to the ticket sales outlet. Buyers can buy tickets via smartphones or laptops by accessing this bus ticket booking website. Not only simplifying the ticket buying process, it can also help reduce the crowds that could be generated in the process of buying and selling tickets. So that the existence of a bus ticket booking website is expected to help reduce the number of people exposed to the corona virus as well as simplify and shorten transactions made by buyers.